Creative crafts for kids over 100 fun projects for two to ten year olds - Dickinson, Gill.; Owen, Cheryl (London Hamlyn, 2009)
Beautiful, sustainable bamboo is one of the most popular materials around for gardens and home décor, the "it" plant of the green movement. This highly regarded introduction to the material, revised and updated, offers rich history, fascinating background and great projects, and illustrates how to contain bamboo in the landscape. It covers all the tools and techniques you need for harvesting, storing, and making things with bamboo. Thirty how-to projects include bamboo fences, trellises, chopsticks, teacups, and even an outdoor shower.--From publisher description.
Includes index.
Keywords: Handicraft -- Juvenile literature; Holiday decorations -- Juvenile literature; Cooking -- Juvenile literature